The SARS-coronavirus nsp7+nsp8 complex is a unique multimeric RNA polymerase capable of both de novo initiation and primer extension. - te Velthuis, A; van den Worm, S; Snijder, E (2012)
Uniquely among RNA viruses, replication of the ~30-kb SARS-coronavirus genome is believed to involve two RNA-dependent RNA polymerase (RdRp) activities. The first is primer-dependent and associated with the 106-kDa non-structural protein 12 (nsp12), whereas the second is catalysed by the 22-kDa nsp8. This latter enzyme is capable of de novo initiation and has been proposed to operate as a primase. Interestingly, this protein has only been crystallized together with the 10-kDa nsp7, forming a hexadecameric, dsRNA-encircling ring structure [i.e. nsp(7+8), consisting of 8 copies of both nsps]. To better understand the implications of these structural characteristics for nsp8-driven RNA synthesis, we studied the prerequisites for the formation of the nsp(7+8) complex and its polymerase activity. We found that in particular the exposure of nsp8's natural N-terminal residue was paramount for both the protein's ability to associate with nsp7 and for boosting its RdRp activity. Moreover, this 'improved' recombinant nsp8 was capable of extending primed RNA templates, a property that had gone unnoticed thus far. The latter activity is, however, ~20-fold weaker than that of the primer-dependent nsp12-RdRp at equal monomer concentrations. Finally, site-directed mutagenesis of conserved D/ExD/E motifs was employed to identify residues crucial for nsp(7+8) RdRp activity.